Relationship between health-related quality of life and burden of disease with functional fitness in women with chronic venous disease : a cross-sectional study - LIMA JÚNIOR, Dalton Roberto Alves Araujo de (2019)
Chronic venous disease (CVD) is defined as a visual and functional manifestation of abnormalities in peripheral venous system that either present or not symptoms causing alterations in superficial and deep veins. In addition, the Aberdeen Varicose Vein Questionnaire (AVVQ) is commonly used to verify the burden of CVD and quality of life of the patients with the disease, enhancing information of the patients. Therefore, the functional fitness and the calf muscles in patients with CVD presents itself as one of the pathways to maintain a healthy venous system and better quality of life, or even in some cases, to control and reduce the severity of the disease. The aim of the study was to verify the relationship between quality of life and burden of disease with functional fitness in women with CVD. This is a cross-sectional study comprised of 47 women that present symptoms of CVD. Following recruitment, patients visited the laboratory to answer the AVVQ and sociodemographic questionnaires. The AVVQ measures the quality of life and burden of disease through the pain and dysfunction, extent of varicosities, complications, and overall domains. In the second visit, anthropometric measurements and a familiarization were carried out. Subsequently, for the functional fitness, it was measured endurance, strength, flexibility, agility and dynamic balance, and calf endurance were performed. Multiple linear regression analyzed and adjusted the data for age, body mass index, and monthly income. In the endurance test, a relationship was found for pain and dysfunction in adjusted model (p = 0.032). In the upper- and lower-body strength test, a relationship was found for pain and dysfunction in the crude analysis and after adjustments (p<0.05) as well as for the overall domain (p<0.05). In the upper-body flexibility test, the crude and adjusted models presented significant relationships with pain and dysfunction (p<0.05). For the agility and dynamic balance test, only the adjusted model related with pain and dysfunction and overall domains (p<0.05). In the calf endurance test, a relationship was found for pain and dysfunction in the adjusted model (p = 0.002). Quality of life and burden of disease are related to functional fitness. Pain and dysfunction and overall domains are the most related to functional fitness, presenting relationship with endurance, strength, and agility and dynamic balance. Thereby, since our study has shown the possible influence of functional fitness on women with CVD, mainly on the pain and dysfunction domain, future controlled and randomized studies should be performed to verify precisely the effect of functional fitness on quality of life and symptoms in CVD patients.